2011
DOI: 10.1371/journal.pone.0018484
|View full text |Cite
|
Sign up to set email alerts
|

Readability of the Written Study Information in Pediatric Research in France

Abstract: BackgroundThe aim was to evaluate the readability of research information leaflets (RIL) for minors asked to participate in biomedical research studies and to assess the factors influencing this readability.Methods and FindingsAll the pediatric protocols from three French pediatric clinical research units were included (N = 104). Three criteria were used to evaluate readability: length of the text, Flesch's readability score and presence of illustrations. We compared the readability of RIL to texts specificall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…Results from our sample demonstrate that the language used in PICFs for research conducted in the field of anaesthesia in Australia and New Zealand exceeds the NHMRC recommended grade eight readability level. This is consistent with international studies of PICFs in other medical fields [16][17][18][19][20][21][22][23] . The two readability formulas achieve different scores for the same document because they count syllables differently depending on which part of the world they were developed (SMOG from England, Flesch-Kincaid from the USA).…”
Section: Discussionsupporting
confidence: 90%
“…Results from our sample demonstrate that the language used in PICFs for research conducted in the field of anaesthesia in Australia and New Zealand exceeds the NHMRC recommended grade eight readability level. This is consistent with international studies of PICFs in other medical fields [16][17][18][19][20][21][22][23] . The two readability formulas achieve different scores for the same document because they count syllables differently depending on which part of the world they were developed (SMOG from England, Flesch-Kincaid from the USA).…”
Section: Discussionsupporting
confidence: 90%
“…In one study, analysed forms had a Flesch Reading Ease comparable with academic journals . A comparison between research information and non‐medical texts illustrates this gap: a large difference was found for the Flesch Reading Ease . The third study described the development of research information material together with children, resulting in a Flesch Reading Ease of 86.3 and Flesch–Kincaid grade of 3.9 for children aged 6–12 years old …”
Section: Resultsmentioning
confidence: 99%
“…One study assessed readability of pediatric consent forms in the United States and showed an average reading level comparable to a university reading level (Tarnowski, Allen, Mayhall, & Kelly, 1990). A study in France compared research information for children to nonmedical texts for children, such as novels (Menoni et al, 2011). The readability of research information was considerably poorer than the readability of nonmedical texts.…”
Section: Readability Gapmentioning
confidence: 99%